The Effectiveness of the Work of Non-Entrepreneurship Soldiers at the Jakarta National Air Defense Command Headquarters - Shobirin Shobirin (Green Publisher Indonesia, 2022)
This research is a quantitative-research. This study aims to discuss the influence of work activities through competence and technology with commitment as mediation. The research method used in this study is a quantitative descriptive approach with a survey method. The type of data used in this study is kuantitative data, which is categorized into two types, namely primary data and secondary data. data were obtained through a questionnaire survey with a population of 183 personnel with a total sample of 103 personnel. The data collectiontechniques used in this study were observation, questionnaire and research. These data were analyzed with SPSS 23 and then conclusions were drawn. The results of the study concluded that each variable consisting of competence, mastery of technology has a significant effect on work activities through commitment as mediation. The path coefficient of each variable i.e. X1 against Y is 0.298with t counting 4.975 > t table 1.97. X1 against Y is 0.328 with t counting 5.521 > t table 1.97. X1 against Y is 0.287with t counting 4.685 > t table 1.97. X1 against Y is 0.277with t counting 3.965 > t table 1.97. X1 against Y is 0.257with t counting 3.682 > t table 1.97. X1 against Y is 0.246 with t counting 3.420> t table 1.97.